Gender, Conflict and Peace-Building in Africa: A Comparative Historical Review of Zulu and Igbo Women in Crisis Management - Ani, Kelechi Johnmary; Uwizeyimana, Dominique Emmanuel (International Journal of Criminology and Sociology, 2021)
The male gender has often dominated the quest for societal security. Analysis and studies on security management and peace-building tend to advance the role of the male folk more than their female counterparts. This study traced the role of historic Zulu women in societal security management and compared it to the Aba Women’s War that is popularly referred to as the Aba women riot. The study used the African developmental feminism theory to anchor its analysis. It maintained that these women rose at critical times to challenge the forces that planted insecurity in their societies. It found that they engaged in both strategic and reactive peace-building. The study also reveals the similarities and differences in Zulu and Igbo women intervention in conflict and security management. Finally, the researchers recommended considering the widespread nature of insecurity in many remote parts of Africa that have consistently led to the death of women and children. There should be a re-awakening of female security regiments in many African societies, and they should be trained to secure their lives and properties through community policing efforts.